2019
DOI: 10.17707/agricultforest.65.4.09
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Wood Quality of Trees in Primary Forests in the Southern Carpathians

Abstract: Functional mechanisms in primary forests can help us discover structural models that can be applied to managed forests. Wood quality is important in silviculture because it influences timber price. Using the structure and tree form of primary forests in the Southern Carpathians as a model, our research objectives were to determine the relationships between wood quality and factors such as coenotic position of trees, the ratio of diameter at breast height (DBH) to tree height, and tree slenderness. Wood quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Research developed in the Southern Carpathians has shown that uneven-aged forests are superior to even-aged forests due to their greater continuity, stability, and protection for trees [16]. In uneven-aged forests from the Southwestern Carpathians, Ciceu et al's equations have been developed in order to predict the diameter distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Research developed in the Southern Carpathians has shown that uneven-aged forests are superior to even-aged forests due to their greater continuity, stability, and protection for trees [16]. In uneven-aged forests from the Southwestern Carpathians, Ciceu et al's equations have been developed in order to predict the diameter distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Structural characteristics of old-growth forests are important starting points for defining the goals in forests that are managed on a regular basis (Vasic et al, 2018) and represent a worthy model for management and structuring of managed forests. Natural selection in primary forests may provide solutions for forest management that could lead to stands with higher stability and superior wood quality (Chivulescu et al, 2019). The significance of this research according to Bosela et al (2015) is also resembled in the fact that there is modest knowledge about competitive and facilitative interactions between trees and species in the mixed spruce-fir-beech forests.…”
Section: Introductionmentioning
confidence: 99%
“…Old-growth stands have developed for a long period of time without relevant human impact. Structural characteristics of old-growth forests represent a worthy model for management and structuring of managed forests (Motta et al, 2015;Vasic et al, 2018;Chivulescu et al, 2019;Curovic et al, 2020). Mixed coniferous and deciduous forests in the area of beech, fir and spruce forests in Bosnia and Herzegovina occupy 716.200 ha.…”
Section: Introductionmentioning
confidence: 99%